A Quality Improvement Initiative to Reduce Blood Culture Contamination in the Neonatal Unit. Issue 3 (19th May 2021) - Allen, Elizabeth; Cavallaro, Angela; Keir, Amy K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Peripheral blood culture contamination (BCC) can lead to an initiation of unnecessary antimicrobial treatment, further laboratory tests, increased length of stay, and increased costs. This study describes a 12-month quality improvement (QI) program to reduce the BCC rate in a neonatal unit by 50%. Methods: The QI team focused on standardizing processes to align with best practices using process mapping and cause and effect diagrams. Plan-Do-Study-Act (PDSA) 1: inoculation of blood culture bottles with the introduction of transfer device; PDSA 2: preparation of the skin for peripheral intravenous cannula insertion; PDSA 3: aseptic technique education package; and PDSA 4: optimizing blood volume of blood collected for culture. The team used statistical process control methodology to detect special cause variation. Results: Compliance with the standard processes as part of PSDA 1 improved from a mean level of 50% to 100% and for PDSA 2 improved from a mean level of 50% to 95%. After implementation of PDSA 3, scores on a relevant knowledge test increased from a mean of 39% (pretraining test; n = 10) to 92% (posttraining test; n = 10) ( P < 0.001). Postimplementation of the processes for PDSA 4, a minimum of 1 mL was collected in 94% of blood culture collection events (n = 450) (mean 1.1 mL; range 0.5–3.5 mL). Special cause variation occurred after the implementation of the PDSA cycles. During the baseline period, the BCC rate was 2.0% and decreased to 1.0% postinterventions implementation. Conclusions: Interventions focused on standardizing practices around collection of blood cultures in neonates were associated with fewer contaminants. This study is reported according to the SQUIRE 2.0 guidelines.